POTENSI EKSTRAK ETANOL DAUN KELAKAI (Stenochlaena Palustris (Burm.f) Bedd) SEBAGAI AKTIVITAS ANTIFUNGI TERHADAP Candida albicans: POTENTIAL ETANOL EXTRACT OF KELAKAI LEAVES (Stenochlaena Palustris (Burm.f) Bedd) AS ANTIFUNGI ACTIVITY AGAINST Candida albicans - Wahyudi, Achmad Nur; Soemarie, Yulistia Budianti; Fauzi, Muhammad (JFL : Jurnal Farmasi Lampung, 2024)
Thrush is caused by various factors, one of which is the growth of Candida albicans fungus in the mouth area. Many antifungal drugs available to treat Candida albicans fungal infections are made from synthetic chemicals that have the risk of side effects. The objective of this research is to determine the antifungal activity of ethanol extract of kelakai leaves (Stenochlaena palustris (Burm.) Bedd against Candida albicans. The research process begins with testing the concentration of ethanol extract of kelakai leaves (Stenochlaena palustris (Burm.f.) Bedd by 50%, 55%, 60%, and 65%. In addition, phytochemical screening tests, specific and non-specific parameter tests were carried out. Phytochemical screening results show that ethanol extract of kelakai leaves is positive for alkaloids, saponins, tannins, and flavonoids. The specific parameter test shows that the water soluble extract content and ethanol soluble extract content are 83.3% and 85.7%, respectively. Non-specific parameter tests showed ash content of 0.25%, drying shrinkage of 0.27%, and specific gravity of 0.798 g/mL. The results of the antifungal activity test indicate that ethanol extracts of kelakai leaves at concentrations of 50%, 55%, 60%, and 65% cannot inhibit the growth of Candida albicans fungi. Keywords: Stenochlaena palutris, Candida albicans, Kelakai, Antifungal